Soil organic carbon and its influencing factors in Nepalese forest ecosystems - Kaﬂe, Gandhiv (Journal of Agriculture and Natural Resources, 2024)
The importance of soil organic carbon (SOC) in climate regulation and sustainable ecosystem management is increasingly recognized, prompting a comprehensive review of SOC research in Nepal. The objective of this study was to consolidate findings from various empirical studies to provide a holistic understanding of SOC dynamics across Nepalese forests. By integrating data from multiple studies derived from online search and desk reviews, this study seeks to identify patterns and factors influencing SOC stocks, thereby informing more effective land management and conservation strategies. The analysis was prepared based on the articles published in the last 100 years (1925-2024). The collected data were synthesized to identify patterns and key factors influencing SOC stocks in Nepalese forests. A narrative synthesis approach was used to integrate findings across studies, providing a comprehensive understanding of SOC dynamics and sequestration potential in the region. This study highlights the critical role of forest ecosystems in carbon sequestration and the influence of factors such as altitude, slope, canopy cover, and forest type on SOC stocks. The findings indicate that altitude, forest type, and management practices are key factors influencing SOC stocks, with greater carbon accumulation noted in pristine and well-maintained forests. This study highlights the significant role of SOC in climate regulation and sustainable ecosystem management. Advanced techniques like remote sensing and machine learning enhance SOC assessment accuracy, yet challenges such as deforestation and soil erosion persist. Sustainable practices, including conservation agriculture and agroforestry, are essential for SOC sequestration. Interdisciplinary collaboration, policy engagement, and community involvement are crucial for promoting these practices and addressing the challenges of SOC management, contributing to global climate change mitigation efforts.